2010
DOI: 10.1086/652276
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Terahertz Transparency and Stability above Dome A, Antarctica

Abstract: ABSTRACT. We present the first direct measurements of the terahertz atmospheric transmission above Dome A, the highest point on the Antarctic plateau at an elevation of 4.1 km. The best-quartile atmospheric transmission during the Austral winter is 80% at a frequency of 661 GHz (453 μm), corresponding to a precipitable water vapor column of 0.1 mm. Daily averages as low as 0.025 mm were observed. The Antarctic atmosphere is very stable, and excellent observing conditions generally persist for many days at a ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…The Antarctic plateau offers a number of unique advantages for precision, ground-based, time-domain as-tronomy, such as the ability to observe continuously during winter, low scintillation noise, excellent seeing above a very low boundary layer, low airmass variations, low aerosols, low water vapor, more stable atmospheric transmission, wider wavelength windows, and a dark sky in the infrared (Lawrence et al 2004(Lawrence et al , 2006(Lawrence et al , 2008Moore et al 2008;Kulesa et al 2008;Aristidi et al 2009;Burton 2010;Zou et al 2010;Yang et al 2010;Sims et al 2010;Bonner et al 2010;Lascaux et al 2011;Tremblin et al 2011;Pei et al 2011Pei et al , 2012Sims et al 2012a,b;Giordano et al 2012;Storey 2013;Hu et al 2014;Ashley 2013;Yang et al 2016). There is thus considerable interest in overcoming the technical challenges of operating in Antarctica, so that the advantages for astronomy can be realized (Tothill et al 2008;Kulesa et al 2008;Crouzet et al 2010;Chapellier et al 2016;Mékarnia et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Antarctic plateau offers a number of unique advantages for precision, ground-based, time-domain as-tronomy, such as the ability to observe continuously during winter, low scintillation noise, excellent seeing above a very low boundary layer, low airmass variations, low aerosols, low water vapor, more stable atmospheric transmission, wider wavelength windows, and a dark sky in the infrared (Lawrence et al 2004(Lawrence et al , 2006(Lawrence et al , 2008Moore et al 2008;Kulesa et al 2008;Aristidi et al 2009;Burton 2010;Zou et al 2010;Yang et al 2010;Sims et al 2010;Bonner et al 2010;Lascaux et al 2011;Tremblin et al 2011;Pei et al 2011Pei et al , 2012Sims et al 2012a,b;Giordano et al 2012;Storey 2013;Hu et al 2014;Ashley 2013;Yang et al 2016). There is thus considerable interest in overcoming the technical challenges of operating in Antarctica, so that the advantages for astronomy can be realized (Tothill et al 2008;Kulesa et al 2008;Crouzet et al 2010;Chapellier et al 2016;Mékarnia et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Schneider et al 2009;Tremblin et al 2011;Matsushita et al 1999;Peterson et al 2003) have already shown that a few sites are well-suited to submm/mid-IR, and FIR-astronomy and their transmission properties are rather well determined (for example by Fourier transform spectrometer obervations in the 0.5-1.6 THz range at Mauna Kea/Hawaii; Pardo et al 2001). The high-altitude (>5000 m) Chilean sites are known for dry conditions (see Matsushita et al 1999;Peterson et al 2003), and site testing is now being carried out at the driest place on Earth, Antarctica (see Chamberlin et al 1997;Yang et al 2010;Tremblin et al 2011). Comparisons between Antarctic and Chilean sites are difficult and uncertain since they rely on ground-based instruments that use different methods and calibration techniques (see Peterson et al 2003, for example).…”
Section: Introductionmentioning
confidence: 99%
“…However, these SN type Ia standard candles are more accurate when measured in the near-IR than in the optical (Barone-Nugent et al, 2012). Improved measurements of the distance scale All parameters quoted from the literature (Zhou et al, 2010b;Yang et al, 2010;Bonner et al, 2010). …”
Section: Supernovae and The Expansion Of The Universementioning
confidence: 99%